2020
DOI: 10.2174/1874944502013010441
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ Knowledge, Attitude, and Performance about Disaster Management: A Case of Iran

Abstract: Background: Iran is a disaster-prone country in which many natural and man-made disasters happen every year. Because the health sector is vital due to its nature of treatment and rehabilitation of the injured after the disasters, all health care providers, especially hospital nurses, should be prepared to provide the services they need. Objective: The present study aimed to determine the level of knowledge, attitude, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 9 publications
1
10
0
Order By: Relevance
“…This finding is in line with that of a previous study showing that nurses with the ideal length of work history can have increased productivity, performance, and ability in providing care. [27][28][29][30] However, it should be noted that nurses who have worked for a long time with a heavy workload can experience decreased productivity due to boredom and burnout when working as a disaster nurse. 31,32 One surprising finding of this study was that nurses who had not participated in disaster training had a greater likelihood of having a higher level of disaster preparedness than those who had engaged in such training.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is in line with that of a previous study showing that nurses with the ideal length of work history can have increased productivity, performance, and ability in providing care. [27][28][29][30] However, it should be noted that nurses who have worked for a long time with a heavy workload can experience decreased productivity due to boredom and burnout when working as a disaster nurse. 31,32 One surprising finding of this study was that nurses who had not participated in disaster training had a greater likelihood of having a higher level of disaster preparedness than those who had engaged in such training.…”
Section: Discussionmentioning
confidence: 99%
“…They reported that the knowledge level of physicians and nurses was satisfactory [ 27 ]. A study in Iran showed that the nurses’ knowledge was moderate [ 28 ]. The authors also found a significant relationship between knowledge score and respondent’s age and job experience.…”
Section: Discussionmentioning
confidence: 99%
“…Nofal et al (2018) discovered that the attitude of the hospital staff in Saudi Arabia was neutral [ 27 ]. Far et al (2020) indicated that the level of attitude of the nurses in Iran was just moderate [ 28 ]. Ahayalimudin and Osman (2016), in their study findings in Malaysia, showed that the physicians, nurses, and assistant medical officers’ attitudes towards disaster management were optimistic [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations